Cool Parent Syndrome; Redefining Cool - Amgain, Ganesh (Europasian Journal of Medical Sciences, 2019)
Parenting style also called parental behaviour is the way parents generally relate to their children.1 It is the overall emotional climate in which parents raise their children. It has been divided into four different categories; Authoritative, Authoritarian, Permissive and Uninvolved. Experts recommend parents to follow authoritative parenting styles to the most effective one. But in Nepalese context, authoritarian parenting style runs among the families. Researches have shown that Nepalese parenting style could not be incorporated into a single parenting style as suggested by Baumrind.2 Present day’s parents in Nepalese context, with all the education and modernization, not setting clear rules for the children, and provision of more than enough freedom is found to be cool. Most of the parenting studies only find the correlation between parenting styles and outcomes rather than cause and effect. That’s why, rather than sticking to the specific type of parenting style or be cool with them, it’s crucial to take time and be able to connect to them and address the needs of the children.